After History: Famine Plays of an Gorta Mór and the Holodomor. - Schmidt, Alyssa. (2017)
Abstract: The extraordinarily divisive nature of famine has inspired few plays that respond to these devastating crises. Drawing on text and performance analysis as well as personal interviews, this dissertation examines plays that represent Ireland's an Gorta Mór and Ukraine's Holodomor. This dissertation addresses the following questions: How does drama contribute to or challenge current notions of the efficacy of famine narratives? How can the famine play expand our ecological awareness of famine in a non-metaphorical sense, in terms of place and food systems? Chapter One establishes context for the relative absence of dramatic responses to an Gorta Mór. An analysis of the melodramatic tensions throughout the production of popular dramatist Hubert O'Grady's The Famine demonstrates a characteristic ambiguity in Famine representation. An analysis of W.B. Yeats's The Countess Cathleen follows, exploring dramaturgical concerns relative to the materiality of the crisis. Chapter Two considers the development of the modern famine play in tandem with growing historiographical interest in the event, especially its agricultural context. Famine by Tom Murphy is a powerful counterpoint to the argument that the Famine defies representation. Chapter Three explores educational and ecological theatre pieces within contemporary Ireland, such as schoolteacher Jim Minogue's play The Flight to Grosses Île and Deirdre Hines' environmentally apocalyptic Ghost Acreage at Vixen Time. In Chapter Four, I assert the importance of an urgent field of study, drama of the Holodomor. The Ukrainian "terror famine" historiography's dependence on oral testimony is analyzed in light of the Ukraine's historically metatheatrical relationship with food in particular. After considering the controversial productions of early Soviet Ukrainian drama, this chapter examines two plays, Bohdan Boychuk's Holod and Natal'ia Vorozhbit's Royal Shakespeare Company-commissioned play, The Grain Store, highlighting their overt depiction of the effects of starvation on communities and individuals. Theatrical representation of famine is innovative, problematic, and unequivocally ambitious. Ultimately, this analysis of representative plays from the late nineteenth to the early twenty-first century not only extends the documentation of the plays of Irish and Ukrainian playwrights heretofore overlooked, but also determines the ecological significance and dramaturgical potential of the "famine play."; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Drama.; Advisor: Downing Cless.; Committee: Laurence Senelick, Barbara Grossman, and Marjorie Howes.; Keywords: Theater, Modern history, and Agriculture.